Theoretical Aspects of NonTraditional English Language Lessons (Eurasian Journal of Learning and Academic Teaching, 2023)
This article deals with the non-traditional types of lessons, which can be used in English classes. We will touch upon, in an attempt to reveal the importance of research in the selection and implementation of the optimal methods and techniques for language teaching and learning.